ASPECTOS IMUNOLÓGICOS E FISIOPATOLÓGICOS DO HIPOTIREOIDISMO DE HASHIMOTO (REMUNOM, 2024)
Hashimoto's Thyroiditis is an autoimmune inflammatory disease of the thyroid, characterized by the production of antibodies targeting the thyroid gland, leading to chronic inflammation responsável for the hypothyroidism typical of this condition. The immune response involves the activation of T lymphocytes (auto-reactive CD4+ and cytotoxic CD8+) and B cells that produce antibodies. This study aimed to review the immunological aspects involved in the development of Hashimoto’s Thyroiditis, focusing on understanding its pathogenesis, physiopathology, and the body’s exacerbated response to this autoimmune disease. The findings indicate that Hashimoto's Thyroiditis seems to be triggered by an initial inflammatory event followed by a specific auto-reactive immune response. It is essentially characterized by the production of autoantibodies to thyroglobulin (TG) and thyroid peroxidase (TPOAb) against thyroid proteins, as well as extensive lymphocytic infiltration that causes tissue inflammation, ultimately leading to glandular destruction.